Menjalin Kedekatan Emosional melalui Komunikasi Hati dalam Hubungan Karyawan dan Pelanggan di Hotel Masainn - Rani, Dewa Ayu Angga; Anggreni, Ni Wayan Yuli (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to examine the application of heart-centered communication based on Nonviolent Communication (NVC) Theory in interactions between employees and guests at the Masainn Hotel, Kuta, Bali. NVC, developed by Marshall Rosenberg, stresses empathetic engagement built on four core components: observation, feelings, needs, and requests. Using a descriptive qualitative approach, data were collected through in-depth interviews with guests and direct field observations of daily service interactions. The findings indicate that employees consistently apply empathy-driven communication by offering warm greetings, attentive service, and genuine emotional presence. These behaviors help create a family-like environment that makes guests feel comfortable and emotionally connected to the hotel. Notably, one guest reported returning to the hotel for three consecutive years, having been introduced by a friend who has been a loyal customer for nine years. This demonstrates that NVC-based communication contributes significantly to guest satisfaction, trust, and long-term loyalty. Furthermore, the study highlights the strategic role of emotional intelligence and compassionate communication in shaping service quality within the hospitality industry. By integrating NVC principles into daily service practices, hotels can foster stronger interpersonal relationships, enhance guest experiences, and build sustainable customer retention.